Improving Students’ Reading Comprehension Improving the Students’ Writing Recount Text Ability by Using Think Talk Write and Self-Regulated Strategy Development - Tasvil Kristin Yavernidar Zebua; Kammer Tuahman Sipayung; Erika Sinambela (LP2M STIT Palapa Nusantara, 2023)
Based on research conducted at SMA Negeri 2 Alasa, researchers found that there were several problems in learning to write English faced by students at SMA Negeri 2 Alasa. Students often have difficulty composing a paragraph by writing down their own ideas. Therefore, researchers conducted research entitled